MANAJEMEN SEKOLAH MUSLIM MINORITAS: Menguji Kontribusi Kepemimpinan Kepala Sekolah pada Kinerja Guru di Papua Barat - Agus Yudiawan; Faradillah Wirjaza Putri (IAIN Sorong, 2020)
Educational governance in schools is closely related to the concept of leadership and the quality of teacher work. Of course, a good leader must be able to understand and carry out various leadership functions in moving his teacher. So that the goals of the educational institutions he leads can be realized immediately. This study aims to examine the principal's leadership function and its contribution to teacher performance in minority Muslim schools. This study used a quantitative descriptive approach with a population of 30 teachers. The entire population was sampled using the saturated sampling technique. Data were collected by distributing questionnaires and analyzed descriptively and inferentially. The inferential analysis used a simple linear regression model. The results showed that: principals were able to carry out leadership functions well (76,7%), teacher performance is in the medium category (59,8%), and principal leadership contributes positively and significantly to teacher performance in Muslim minority areas. It can be concluded that, if the leadership functions are carried out properly, the teacher's performance will increase.